Social economic crises and conversion of the management of the Olympic movement: the impact on the models of development of the upcoming Olympic Games - Валентин Зуев; Павел Смирнов (National University of Physical Education and Sport of Ukraine, 2016)
The paper attempts to provide an evidence-based forecast for the development of the Olympic Games for the next 16-20 years using the methods of virtual simulation, content analysis and retrospective analysis. The authors studied social economic crises and conversion of the management of the Olympic movement and their impact on the models in the development of the upcoming Olympic Games. Three models of the development of the Olympic Games are proposed as follows: «Optimistic», «Real optimal» and «Pessimistic». Probabilistic existence of each model were investigated in the different aspects and taking into account the availability of certain social economic and political conditions. The most probable ones, according to the authors opinion, is the «Real optimal» model. The difficulties and obstacles were identified that may arise on the course of the Olympic movement: change in the number of countries participating in the Olympic Games; the number of fans and viewers; preservation and expansion of the number of sports in the Olympic program.